Enhancing Corporate Governance through Effective Oversight and Accountability - Sari, Ratna (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
The purpose of this study is to explore the multifaceted nature of corporate governance, focusing on the interplay between oversight mechanisms and accountability frameworks. Through a comprehensive review of scholarly literature and empirical research findings, this paper examines the role of various governance mechanisms, including boards of directors, internal control systems, and accountability mechanisms, in shaping governance practices and outcomes. The research design involves a qualitative synthesis of existing literature, supplemented by insights from interdisciplinary perspectives such as economics, law, management, and sociology. Findings highlight the critical importance of board composition, independence, and expertise in enhancing governance effectiveness and mitigating agency conflicts. Additionally, the study underscores the significance of internal control systems, risk management processes, and external accountability mechanisms in fostering transparency, fairness, and trust among stakeholders. The implications of these findings extend to academia, where the research contributes to a deeper understanding of corporate governance complexities, and to practice, where organizations can leverage insights to strengthen their governance frameworks and foster stakeholder trust.